Reinstatement of the independent specific status of Chrysanthemum neo-oreastrum (Asteraceae, Anthemideae) - Chi, Xiao-Rui; Wang, Long (Phytotaxa, 2022)
Chrysanthemum neo-oreastrum (Asteraceae, Anthemideae) has been placed in synonymy with C. hypargyreum. Based on our examination of herbarium specimens and field investigation, C. neo-oreastrum was found to be easily distinguishable from C. hypargyreum morphologically. Its independent specific status is therefore resurrected. An emended description and a distribution map are also provided for this species.